PENGARUH PERSIAPAN PRANIKAH, LINGKUNGAN PRE DAN POSTNATAL TERHADAP PERTUMBUHAN DAN PERKEMBANGAN BALITA DI KABUPATEN SOLOK - Suciana, Sri; Wildayani, Desi; Lestari, Widya (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Introduction: The first five years of a child's life (toddler) is the fastest growing and developing period in the human brain, this period is a very sensitive but also critical period for the child's brain in receiving various inputs / learning / influences from the surrounding environment, and nutritional intake. It is at this time that children have the opportunity to develop aspects in themselves, both physically, cognitively and socio-emotionally. The growth of toddlers is assessed from the anthropomentri of the toddler. The indicator that researchers use refers to regulation of the minister of health No.2 of 2020 on child anthropometric standards. The purpose of the study was to analyze the relationship of prenatal preparation, prenatal environment, delivery environment, and post-Christmas with the growth and development of children in mothers who have children under five in Kanagarian Taruang-taruang Working Area Lasi River Health Center Solok in 2020. Method: This research is a type of analytical research and has been conducted in The Kanagarian Taruang-taruang Working Area of Puskesmas Lasi Solok in July - September 2020. The population of this study was mothers who had children who were 5 years old and the sample was toddlers who came to posyandu and who were in the working area of Puskesmas Lasi and met the criteria of inclusion (consecutive sampling) of 45 people. Data processing through editing, coding, data entry, cleaning, and tabulating stages. The processed data is then analyzed using univariate and bivariate (chi square). Result: Out of 45 respondents, 18 toddlers (40%) were found who have nutritional status with abnormal weight/age indicator, 11 toddlers (24.2%) with abnormal nutritional status of height/age, weight/height 16 people (35.6%) abnormal, did not do pre-marital preparation 23 people (51.1%), did not get a good antenatal environment as many as 17 people (37.8%), did not get a good delivery environment as many as 17 people (37.8%), did not get a good postnatal environment as many as 22 people (48.9%), and the development of dubious toddlers according to the age of toddlers as much as 9 people (20%). Conclusion: There was a meaningful relationship between the postnatal environment and the growth of toddlers based on weight/age indicators, whereas, pre-marital preparation variables, antenatal environment, and delivery environment have no meaningful relationship with the growth and development of the child.